You are on page 1of 3

1.

Pattern
Considering this 2 x 2 system of linear equations:
x + 2y = 3
2x y = -4
While Examining the first equation, we see a pattern in the constants of the
equation, i.e. 1 is the constant preceding the variable x, and 2 precede y and the
equation equals 3. The constants have a common difference of 1 between them:
21=1
32=1
Going forward from this, we can say that the constants in the first equation belong
to an arithmetic series(of progression) with a common difference of 1.
Looking at the second equation, we also observe that the constants are
consecutive members of and arithmetic series(of progression), this time with
common difference of -3.
-1 -2=-3
-4 - (-1) = -3

2.Significance of the solution


In the system A1/A2 B1/B2 .Therefore , intersecting lines will be formed and we
will get a unique solution. The point of intersection of the two lines ie.(-1,2) is the
solution. From the graph, we get that x= -1 and y = 2.

3.Examples
1)
2x + 4y = 6 (constants have a common difference (d) of 2)
4x - 2y = -8 (constants have a common difference of (d) -6)
2)
4x +8 y = 12 (common difference of 4)
8x - 4y = -16 (common difference of -12)

5.General statement
Any equation where the constants follow an arithmetic series will give the answer
for y as 2 and for x -1. This suggests that any two lines whose equations that are
similar to these will intersect at the same point
The result suggests that for any two linear equations written in the form:
ax + by = c
dx + ey = f
and there is a common difference in the constants a, b and c, such that:
c-b = b-a
and a common difference in the constants d, e and f, such that:
f-e = e-d
but:
(f-e) or (e-d) (c-b) or (b-a) because if the common difference in the two
equations is the same, this will suggest that the two lines are collinear, and
therefore they will never intersect, and it will not be possible to solve for x and y.
The result will always be (-1,2)
We can generate a general formula for equations similar to these:
let the first term of the first equation be A1 and let if have a common difference of
d.
let the first term of the second equation be B1 and have a common difference of c.
therefore the first equation will look like: A1 x+ (A1 + d) y = (A1 + 2d)
the second equation will look like: B1 x + (B1 + c) y = (B1 +2c)

MATHS
FA 1
project
Syed Sabeeth
10 A